Overwash hazard assessment - Rodrigues, B. A. (2018)
Overwash is a natural storm-related process that occurs when wave runup overcomes the dune crest. Because coastlines are globally occupied, overwash is a hazardous process and there is a need to identify vulnerable areas. This study proposes a method to detect overwash-prone areas in the Ancao peninsula, Portugal, and eventually outlines a vulnerability map. Dune base (D-LOW) and crest (D-HIGH) topography were surveyed. Three different storm scenarios (5-, 10- and 25- year return period storms) and associated waves and sea level were determined. According to these data, extreme wave runup (R-HIGH) was calculated by a parameterisation set for intermediate-reflective beaches. The maps for collision and overwash regimes were designed by comparing R-HIGH values with D-LOW and D-HIGH. Almost the entire dune base along the peninsula is vulnerable to collision regime. The overwash process was identified mainly along the tidal inlet hazard area and within the human-occupied portion of the beach, where overwash is expected to occur within 5 years of return period. The developed method considers the main overwash driving forces and proved to identify hazardous areas previously observed in the area. Occasional differences between modelled and observed overwash areas can be attributable to equipment errors, morphology interpretation subjectivity and maladjustments in runup parameterisation. Nevertheless, the method proved to be effective in reproducing the overall Ancao peninsula vulnerability and can be widely applied. Therefore, it is a simple and potentially important tool for coastal management that enables mitigation strategies for occupied coasts and assessment of geological and ecological consequences in natural areas.